Intravascular lymphoma presenting with hypoxaemia, platypnoea and lactic acidosis. Issue 6 (23rd June 2021) - Englert, Pierre; Levy, Sophie; Vekemans, Marc; De Wilde, Virginie
Abstract : Intravascular large B-cell lymphoma (IVLBCL) is an aggressive and rare type of diffuse extranodal B-cell lymphoma. Diagnosis and treatment are challenging and clinical presentation is variable. Physicians should be aware of this rare but life-threatening lymphoma without adenopathy and treatment should be promptly started. We describe the case of a 70-year-old woman who presented with general malaise, acute dyspnoea, platypnoea and lactic acidosis. Echocardiography revealed an extracardiac shunt, the cause of her orthodeoxia. The patient developed rapid liver failure and underwent liver biopsy. Anatomopathological findings suggested IVLBCL, non-germinal center type. She achieved complete remission after rituximab, cyclophosphamide, doxorubicin, vincristine, methylprednisolone chemotherapy but relapsed 1 year after initial presentation with multiple organ involvement. The patient's relapsed disease was treated with rituximab, iphosphamide, carboplatin, etoposide and she is still in complete remission 2 years later.